EVALUATION OF HEALTH FACILITIES LOCATION TO SUPPORT ACCESSIBILITY TO ESSENTIAL HEALTH SERVICES IN BANDAR LAMPUNG CITY, LAMPUNG PROVINCE, INDONESIA - Rahadianto, Muhammad Ario Eko; Nurhayati, Misfallah; Nugraha, Akbar Wahyu; Anggara, Ongky (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2024)
Health remains one of the most important aspects of every human life, with access to quality healthcare services being a pivotal component of human well-being. In Indonesia, health facility distribution has been characterized by disparities, primarily concentrated on the populous Java Island. This distribution inequity underscores a significant challenge in achieving Sustainable Development Goals (SDGs) under Goal 3, which aims to ensure healthy lives and promote well-being for all. Bandar Lampung, the most densely populated city in Lampung Province and one of Sumatra's most populated cities, experiences an intensified demand for healthcare facilities due to its substantial population. However, the city grapples with numerous infrastructural challenges, including suboptimal road conditions that hinder accessibility to essential healthcare services. These challenges further underscore the urgency of assessing and addressing the healthcare infrastructure within Bandar Lampung. This research seeks to undertake a comprehensive evaluation of health facility availability in Bandar Lampung City, as well as an in-depth analysis of the accessibility of healthcare services in different areas of the city. To achieve this, the study employs the Network Analysis Tool, which leverages road network data to model travel distances and times. In addition to road network data, geospatial population data sourced is integrated into the analysis to gauge the demand for healthcare facilities within Bandar Lampung. This multifaceted approach is essential in comprehensively addressing the complex interplay between supply and demand in the healthcare sector. The combination of these datasets culminates in the creation of an accessibility model that unveils the disparities in healthcare access across Bandar Lampung. The model highlights areas where accessibility to healthcare facilities remains surprisingly low, despite the city's high population density. Conversely, it also identifies regions with high accessibility, potentially serving as templates for improving healthcare distribution in underserved areas. By revealing these disparities, this research contributes valuable insights to healthcare planning and policy formulation in Bandar Lampung and offers a template for addressing similar challenges in other regions with uneven healthcare distribution.